Drug use and its perceived consequences: A comparison of foodservice and non-foodservice employees. (January 2019) - Kaminski, Kristen; Kitterlin-Lynch, Miranda; Cain, Lisa; Beckman, Eric
Highlights: Illicit drug use and abuse is a major problem in the foodservice industry as each year, more and more employees are testing positive for illicit drugs. A survey of foodservice and non-foodservice employees revealed significant differences on demographics and illicit drug-use behavior on age, ethnicity, education, and illicit drug-use. Many of these employees do not consider their drug use and abuse to be a problem and perceive little or no concern about the negative outcomes of illicit drug use. Results indicate foodservice employees are more likely to use illicit drugs and are more concerned with short-term negative outcomes as a result of illicit drug use than the non-foodservice labor force. Illicit drug use prevention efforts are less prominent in the foodservice industry than in other workplaces. Abstract: From 2015 to 2016, positive tests for illicit drugs in the United States increased from 4.0% to 4.2%. This increase reflects a worsening illicit drug-use problem in foodservice and other industries. A survey of foodservice and non-foodservice employees revealed significant differences on demographics and illicit drug-use behavior. Chi-square tests indicated these differences between foodservice and non-foodservice employees on age, ethnicity, education, and illicit drug-use. Independent t-tests indicated a significant difference in illicit drug-use concerns between drug users and non-drug users. Research findings revealed foodservice employees tend to focus primarily on short-term consequences (productivity and lethargy) of illicit drug-use, which may help explain the rampant use of these substances. Foodservice industry professionals need to take a more active role in combating illicit drug use among employees by drug-testing, having clear policies and procedures, increasing accountability and comradery among the workforce, and communicating the long-term negative outcomes of illicit drug use.